Energy transition for sustainable economy: what is the role of government governance and public concern? - Wang, Yunxiao; He, Ziwen; Zou, Jianke; Xie, Henglang; Bao, Junsong (Elsevier, 2024)
The global imperative for sustainable development necessitates a deeper understanding of the factors driving energy transitions. This study examines how government environmental governance and public environmental awareness influence China's shift towards sustainable energy practices. Utilizing a comprehensive dataset from Chinese prefecture-level cities, we analyze the impacts of governmental environmental governance and public concern on energy transition intensity across regions. Our findings reveal that both proactive government investment and heightened public awareness significantly contribute to advancing energy transitions, with notable regional variations. The analysis uncovers complex relationships between local economic conditions, societal engagement, and transition progress, highlighting the need for tailored strategies. These insights contribute to the sustainable development discourse by elucidating the synergistic effects of governance and public engagement in driving energy transitions. Our research offers valuable policy implications for fostering sustainable energy futures, emphasizing the importance of coordinated efforts between governmental structures and public sentiment in achieving meaningful environmental progress.